AN APPLIED INTERLANGUAGE EXPERIMENT INTO PHONOLOGICAL MISPERCEPTIONS OF ADULT LEARNERS - Tench, Paul (International Journal of English Studies, 2001)
The aim of the experiment described here was to attempt to measure adult learners’ percetual interlanguage in phonology. The implementation of a methodology involving context-less lists of English words selected for their potential phonological problems is described, and the way in which learners process words they are listening to is discussed. The results of 13 Korean adults’ perceptions and misperceptions are analysed: the most misperceived vowels were ID:/ and the short vowels /u, A, I, E, D, z/;c onsonants were mainly misperceived in word-final position, but 18, v, b, p, rl were misperceived to some extent in any position, and /S, j/ before the vowel /i:/; consonant clusters involving /f, 1, r/ were particularly subject to misperception. These findings have implications for the design of English pronunciation teaching materials for Koreans.